2016
DOI: 10.1177/0899764016654220
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of an Ethnic Community-Based Organization in the United States

Abstract: Ethnic nonprofit community-based organizations (CBOs) have played a crucial role in the social fabric of ethnic communities. Despite the importance of ethnic CBOs, limited empirical knowledge exists about these types of organizations. This study seeks to fill this gap by exploring how ethnic CBOs engage their target populations in stigma-associated services using a multidimensional cultural competence framework. A case study approach is used to explore how a Korean ethnic organization engages older adults in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Having this tight connection helps such organizations better understand their communities’ needs and how to address them in culturally appropriate ways (Gooden et al, 2018; LaFrance Associates, 2005; Patraporn et al, 2010). Moreover, POC tend to trust these organizations more and are more likely to seek help from them (de Graauw, 2016; Vu et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Having this tight connection helps such organizations better understand their communities’ needs and how to address them in culturally appropriate ways (Gooden et al, 2018; LaFrance Associates, 2005; Patraporn et al, 2010). Moreover, POC tend to trust these organizations more and are more likely to seek help from them (de Graauw, 2016; Vu et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee et al, 2017). To date, only a handful of studies have focused on POC-serving nonprofits and most discuss these organizations in a descriptive manner, focusing mainly on what they do and whom they serve (e.g., de Graauw, 2016; Gleeson & Bloemraad, 2013; Hung, 2007; Vu et al, 2017). Though a growing number of studies have looked at the organizational capacity of POC-led nonprofits (Danley & Blessett, 2022; Fredette & Sessler Bernstein, 2019; Mumford, 2022), we know little about the financial struggles POC-serving and/or POC-led nonprofits face.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that this had implications for managing professional and personal boundaries among staff and clients, as clients saw staff as friends and “like family.” In another study of arts organizations working with disabled artists, the researchers found that the artists built their own media platforms and advocated for their work as well as that of their peers (Onyx et al, 2018, p. 585). Beneficiaries’ support for each other was evident in many articles, (Markström & Karlsson, 2013; Vu et al, 2017). Carnochan et al (2014) provided a more fine-grained example of how NPOs are dependent on the contribution of beneficiaries.…”
Section: Current Research On Nonprofits: Beneficiaries As Organizatiomentioning
confidence: 99%
“…Nonprofit organizations have a long history of service provision and advocating on behalf of vulnerable populations. Nonprofit organizations, and immigrant nonprofits in particular, provide various services to local populations including, for example, cultural and/or educational activities, employment or healthcare assistance, religious guidance, assistance with the immigration process, and language assistance Vu et al 2017). In segregated communities where nonprofit organizations are present, nonprofits appear to mitigate some of the negative effects associated with living in residentially segregated areas, such as connecting residents to other organizations and resources; offering health or other types of information; and reducing levels of crime Small 2006).…”
Section: Segregated Metropolitan Areasmentioning
confidence: 99%
“…Immigrant nonprofits, not only assist people from their target group in culturally and language specific ways, but tend to work with immigrants through common procedures for societal integration into the mainstream society (i.e. finding employment, navigating the healthcare system, religious guidance, and overcoming language and cultural barriers; Vu et al 2017). In addition, immigrant nonprofit organizations may also provide services to the general public.…”
Section: Sensitivity Analysismentioning
confidence: 99%